2013
DOI: 10.4049/jimmunol.1300940
|View full text |Cite
|
Sign up to set email alerts
|

Human SAP Is a Novel Peptidoglycan Recognition Protein That Induces Complement-Independent Phagocytosis of Staphylococcus aureus

Abstract: The human pathogen Staphylococcus aureus is responsible for many community-acquired and hospital-associated infections and is associated with high mortality. Concern over the emergence of multidrug-resistant strains has renewed interest in the elucidation of host mechanisms that defend against S. aureus infection. We recently demonstrated that human serum mannose-binding lectin (MBL) binds to S. aureus wall teichoic acid (WTA), a cell wall glycopolymer, a discovery that prompted further screening to identify a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 50 publications
(68 reference statements)
0
20
0
Order By: Relevance
“…Opsonins are structurally diverse frontline defense molecules that recognize and bind bacteria to mark them for phagocytosis and elimination through specific cell surface receptors 52 . Families of opsonins include antibodies, complement proteins, and factors such as pentraxins (serum amyloid P and Creactive protein) 53,54 , collectins 55 , and ficolins 56 . As each opsonin may have idiosyncratic target specificities and efficacy, the nature and availability of specific opsonins at the sites of infection may affect the pathological outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Opsonins are structurally diverse frontline defense molecules that recognize and bind bacteria to mark them for phagocytosis and elimination through specific cell surface receptors 52 . Families of opsonins include antibodies, complement proteins, and factors such as pentraxins (serum amyloid P and Creactive protein) 53,54 , collectins 55 , and ficolins 56 . As each opsonin may have idiosyncratic target specificities and efficacy, the nature and availability of specific opsonins at the sites of infection may affect the pathological outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the binding and agglutination of Gram-positive bacteria was relatively low. Recent studies have also shown that wall teichoic acid prevents the binding of SAP to PGN [50]. Interestingly, SAP enhances the antibacterial activity of mouse macrophages toward Listeria monocytogenes (a Gram-positive species), and this activity is not associated with the binding of SAP to the pathogen [51].…”
Section: Discussionmentioning
confidence: 99%
“…CRP interacts with phosphocholine (PC) that is present in a number of bacterial structures including the teichoic acid of S. pneumoniae (Volanakis, ). SAP binds a variety of bacterial cell wall structures such as carbohydrates, LPS, and peptidoglycan (Hind et al ., ; Noursadeghi et al ., ; An et al ., ). Alternatively, C1q can bind directly to the bacterial surface to activate the CP.…”
Section: Bacteria Under Stress By Complementmentioning
confidence: 97%